Bank Industry Openness In Indonesia: Control Of Agency Problems - Putu Anom Mahadwartha Mahadwartha (Universitas Airlangga, 2008)
Indonesian banking sector has recently been suffering from bad debt and liquidity problems. Crisis since 1997 has impoverished bank’s performance and reduced shareholder wealth. The deterioration of bank’s performance with respect to bank’s purpose to be an intermediation agent also affects the wealth of stakeholders, especially depositors. Agency problem has severe effects on bank’s performance. Openness policy especially in bank ownership structure also has an effect on competition between banks. Globalization forces early openness on banking industry, therefore foreign ownership in banking industry becomes usual in Indonesia. Central bank has an obligation to support citizen with variety of banking services, without sacrificing security. Although Indonesia has several prospective domesticowned banks, however crisis weakened national banking industry. Therefore, type of ownership should have difference effect on agency problems controlling mechanism. This research examines agency theory arguments in banking industry by analyzing the effect on firm specific variables, which are managerial stock ownership, leverage, dividend yield, and type of ownership. Agency costs proxy by earnings volatility, manager’s portfolio diversification losses, bank size, and standard deviation of bank equity returns. Types of ownership are domestic-owned banks, and foreign-owned banks. It is one of the first researches that examine the determination of financial policy variables based on agency theory perspective in banking industry. This research examines the largest 51 banks during the period of 1999-2004 using quarterly financial report. The result showed bank size and a measure of manager’s portfolio diversification opportunity set affect the bank’s level of managerial stock ownership, leverage, and dividends. The result also confirms the difference effect of type of banks ownership to controlling mechanism of agency problems.